Formulation of Effervescent Granule Telang Flower Essense (Clitoria Ternate L.) and Rimau Gerga Lebong Orange (Citrus Nobilis) as a Health Drink - Herlina, Herlina; Yanuarto, Tri; Mulyani, Elly; Hartati, Yuni (SINTA Journal (Science, Technology, and Agricultural), 2024)
Butterfly pea flowers (Clitoria ternatea L.) contain chemicals, namely anthocyanin flavanoids, which are a subclass of water-soluble flavanoids and are responsible for the color of the flowers. RGL oranges (Citrus nobilis) are a high source of vitamin C which is effective as an antioxidant which can neutralize free radicals. Effervescent granules have high solubility in water making them very easily absorbed and contain carbonates which provide a fresh taste sensation. The aim of making effervescent granules is to find out whether butterfly pea flower essence with RGL oranges can be formulated into effervescent granules and meet the effervescent granule test requirements. Butterfly pea flower essence with RGL orange is formulated with varying concentrations of butterfly pea flower, namely 100; 150; 200 pieces. Effervescent granules are formulated using the dry granulation method. The results of research on making effervescent granules in organoleptic tests have different colors, effervescent granule flow time 1.31 - 1.36 seconds, angle of repose 27° - 29°, water content 1.5 - 1.7%, dissolving time 27.39 – 36.8, all of these tests meet the requirements of the effervescent granule test, granule pH 5.17 – 5.52 which tends to be acidic, this condition is influenced by the addition of RGL butterfly pea flower and orange juice, based on the hedonic test the most preferred formula is F III .